Profile Analysis of Critical Thinking Ability of Science Education Study Program Students - Ita Ainun Jariyah; H. Husamah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
In order to produce superior human resources according to the demands of 21st- century competence and be resilient in facing global challenges in the era of society 5.0, the ability to think critically must be mastered. Critical thinking is a key competency needed by university graduates and most universities have determined this ability as one of the attributes that must be supplied to their graduates. This study aims to analyze the profile of critical thinking skills of Science Education Study Program students. The subjects in this study were 147 students of the Science Education Study Program, Faculty of Tarbiyah and Teacher Training UINSA, class of 2020, 2021, and 2022, totaling 147 students. Critical thinking skills are measured using a critical thinking question instrument consisting of 10 essay questions with 10 indicators of critical thinking skills. The questions tested are questions that have been revised and declared valid by expert validators. The results of the critical thinking ability test are analyzed descriptively to see the category of critical thinking skills in students and each indicator. This study revealed that the critical thinking ability profile of the students of the Science Education Study Program was dominated by the low category, which was 32.3%. Critical thinking indicators that get high categories are indicators of analyzing conclusions, logic classes, and definitions; obtain medium categories on indicators of problem formulation, reasoning ability, and short intervals between observation and report; Getting a low category on indicators assesses the correctness of assumptions, makes and considers decisions, as well as formulates alternative solutions.